Associations between enteric pathogen carriage and height-for-age, weight-for-age and weight-for-height in children under 5 years old in urban Dhaka, Bangladesh. (2020) - Berendes, David; Capone, Drew; Knee, Jackie; Holcomb, David; Sultana, Sonia; Pickering, Amy J.; Brown, Joe
Abstract: Nutritional factors and infectious agents may contribute to paediatric growth deficits in low- and middle-income countries; however, the contribution of enteric pathogens is only beginning to be understood. We analysed the stool from children <5 years old from an open cohort, cluster-randomised controlled trial of a point-of-collection water chlorinator in urban Bangladesh. We compared the presence/absence of 15 enteric pathogens detected via multiplex, molecular methods in the stool with concurrent Z -scores/ Z -score cut-offs (−2 standard deviations (s.d. )) for height-for-age (HAZ/stunting), weight-for-age (WAZ/underweight) and weight-for-height (WHZ/wasting), adjusted for sociodemographic and trial-related factors, and measured caregiver-reported diarrhoea. Enteric pathogen prevalence in the stool was high (88% had ≥1 enteric pathogen, most commonly Giardia spp. (40%), Salmonella enterica (33%), enterotoxigenic E. coli (28%) and Shigella spp. (27%)) while reported 7-day diarrhoea prevalence was 6%, suggesting high subclinical infection rates. Many children were stunted (26%) or underweight (24%). Adjusted models suggested Giardia spp. detection was associated with lower HAZ (−0.22 s.d., 95% CI −0.44 to 0.00; prevalence ratio for stunting: 1.39, 95% CI 0.94–2.06) and potentially lower WAZ. No pathogens were associated with reported diarrhoea in adjusted models. Giardia spp. carriage may be associated with growth faltering, but not diarrhoea, in this and similar low-income settings. Stool-based enteric pathogen detection provides a direct indication of previous exposure that may be useful as a broader endpoint of trials of environmental interventions.